2008
DOI: 10.1159/000151278
|View full text |Cite
|
Sign up to set email alerts
|

Improved Metabolic Control Results in Better Myogenic Response of Retinal Arterioles in Patients with Diabetes Mellitus Type 1

Abstract: Aims: The retina is protected against high blood pressure by the myogenic constriction of arterioles (the Bayliss effect). Hyperglycemia impairs this retinal autoregulation by endothelial dysfunction. The purpose of this prospective pilot study was to test whether improved metabolic control results in a measurable effect on the myogenic response of human retinal arterioles to acute increases in blood pressure. Methods: The Bayliss effect was measured in 25 patients with diabetes mellitus by the Retinal Vessel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…For example, arterioles isolated from biopsy samples of fat from patients with type 2 diabetes fail to constrict in response to pressure but constrict normally in response to norepinephrine. 31 Additionally, the myogenic response of retinal vessels to isometric exercise in patients with type 1 diabetes does increase when glycemic control improves, 34 suggesting that at early stages the impairment is functional. In the latter study, lack of a control group of nondiabetic subjects and lack of information on the individual responses of the diabetic subjects to improved glycemic control preclude definitive conclusions on the frequency and reversibility of the abnormality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, arterioles isolated from biopsy samples of fat from patients with type 2 diabetes fail to constrict in response to pressure but constrict normally in response to norepinephrine. 31 Additionally, the myogenic response of retinal vessels to isometric exercise in patients with type 1 diabetes does increase when glycemic control improves, 34 suggesting that at early stages the impairment is functional. In the latter study, lack of a control group of nondiabetic subjects and lack of information on the individual responses of the diabetic subjects to improved glycemic control preclude definitive conclusions on the frequency and reversibility of the abnormality.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, there is a suggestion that a defective myogenic response in patients without retinopathy is amenable to correction. 34 This would add to the candidate marker the highly desirable characteristic of being a potential surrogate end point for drug studies and a target for early interventions to abort clinical retinopathy. However, we have noted above that the study providing this important suggestion does not permit definitive conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…5B) (2, 137). Interestingly, Blum et al (26) demonstrated that myogenic response of retinal arterioles was significantly improved by proper metabolic control in diabetic patients. Taken together, both experimental and clinical studies provide evidence of the impact of poor glycemic and metabolic control during diabetes on vascular myogenic function.…”
Section: Autoregulation and Myogenic Behaviormentioning
confidence: 99%
“…However, better understanding of its pathogenesis may allow molecular targets to be identified for novel, retinopathy specific treatments. Reduced autoregulatory changes in vascular diameter in responses to changes in O 2 , vascular transmural pressure and retinal stimulation with a flickering light are among the earliest defects of retinovascular function seen in diabetes[ 7 13 ]. This suggests that molecules believed to play a role in the control of vascular tone may be implicated in the diabetic changes in the eye.…”
Section: Introductionmentioning
confidence: 99%